An Introduction to Advertising - Afra Khan (Journal of Advanced Research in Journalism & Mass Communication, 2021)
Promoting is any paid type of correspondence from a distinguished support or source that causes to notice thoughts, merchandise, administrations, or the actual support. Most promoting is coordinated toward bunches as opposed to people, and publicizing is normally conveyed through media like TV, radio, papers and, progressively, the Internet. Promotions are regularly estimated in impressions (the occasions a shopper is presented to a notice). How to cite this article: Khan A. An Introduction to Advertising. J Adv Res Jrnl Mass Comm 2020; 7(4): 1-3.